2022
DOI: 10.3390/curroncol29080415
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Place for Adjuvant Chemotherapy in the Treatment of Locally Advanced Cervical Cancer?

Abstract: Findings on the efficacy of adjuvant chemotherapy (ACT) of locally advanced cervical cancer (LACC) after the concurrent chemoradiation (CCRT) therapy were inconsistent, and the OUTBACK trial was expected to shed some light regarding the topic. Its results on ACT in LACC were negative, with the conclusion of not to use it. The objective of this review was to present the inconsistencies of previous studies, along with the OUTBACK trial in more detail, and to rethink whether its results provide an unambiguous and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
2
0
1
Order By: Relevance
“…The ACT should be performed for the patients with residual disease confirmed by cervical biopsy and/or image-positive lymph nodes (short diameter ≥15 mm) in our trial. Despite the OUTBACK trial shown negative result on ACT, the efficacy of ACT of LACC after CCRT were inconsistent [ 28 29 ]. The experts of our trial consider the residual disease after CCRT as the possible helpful factor in identifying subtype that could derive benefit from ACT.…”
Section: Discussionmentioning
confidence: 99%
“…The ACT should be performed for the patients with residual disease confirmed by cervical biopsy and/or image-positive lymph nodes (short diameter ≥15 mm) in our trial. Despite the OUTBACK trial shown negative result on ACT, the efficacy of ACT of LACC after CCRT were inconsistent [ 28 29 ]. The experts of our trial consider the residual disease after CCRT as the possible helpful factor in identifying subtype that could derive benefit from ACT.…”
Section: Discussionmentioning
confidence: 99%
“…Въпреки ползата за преживяемостта, отчетена в някои от тези проучвания, АХТ все още не се смята за стандарт на лечение (13). Резултатите от текущото проучване OUTBACK (5) (седмична доза Цисплатин по време на ЛХЛ, последвани от четири цикъла Паклитаксел плюс Карбоплатин като адювантна терапия) могат да предоставят допълнителни доказателства за ролята на ХТ в адювантен аспект (5). Последните публикувани резултати от проучването показват, че АХТ след едновременно ЛХЛ не подобрява преживяемост в сравнение с едновременното ЛХЛ, и в групата на АХТ са наблюдавани значително повече нежелани събития (28).…”
Section: ролята на адювантната химиотерапия при лечението на локално ...unclassified
“…A phase III clinical study (OUTBACK Trial) showed that four cycles of adjuvant chemotherapy with Paclitaxel plus Carboplatin following standard CCRT did not prolong patient survival ( 13 ). Most current studies do not recommend adjuvant chemotherapy for LACC patients ( 14 ). Targeted anti-angiogenesis inhibitor therapy with Endostar in combination with CCRT increased the distance metastasis-free survival (DMFS) but did not improve progression-free survival (PFS) ( 15 ).…”
Section: Introductionmentioning
confidence: 99%